Pengaruh Ketersediaan Produk Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Konsumen CV. Alisa - suryaniningsih, Suryaniningsih; Nurlaeli, Fenti; Yolanda, Silvi Yulis (Medikonis, 2024)
Purchase decisions are influenced by several factors, including product availability and word of mouth. This study aims to determine the effect of product availability and word of mouth on purchasing decisions on consumers CV. Alisa.The population in this study are consumers of CV. Alisa and the sample used the slovin formula totaling 97 respondents. Data collection techniques using a questionnaire. The analytical tool used is descriptive analysis. Data processing was carried out using the SPSS Statics Version 26.0 computer software program. The results showed that partially product availability has a positive and significant effect on purchasing decisions while word of mouth has no significant effect on purchasing decisions. The results of the simultaneous analysis of product availability and word of mouth have no significant effect on purchasing decisions at CV. Alisa. Company suggestions to improve service so that consumers are more confident in buying products at CV.Alisa. and companies are expected to pay more attention to the intended marketing channels, so that they are in line with business characteristics.